Mid‐infrared suspended waveguide platform and building blocks. Issue 2 (1st April 2019) - Sánchez-Postigo, Alejandro; Wangüemert-Pérez, Juan Gonzalo; Soler Penadés, Jordi; Ortega-Moñux, Alejandro; Nedeljkovic, Milos; Halir, Robert; El Mokhtari Mimun, Faysal; Xu Cheng, Yolanda; Qu, Zhibo; Khokhar, Ali Z.; Osman, Ahmed; Cao, Wei; et al.
Abstract : In this work, the authors present their recent progress in the development of a platform for the mid‐infrared wavelength range, based on suspended silicon waveguides with subwavelength metamaterial cladding. The platform has some intrinsic advantages, which make it a very promising candidate for sensing applications in the molecular fingerprint region. Specifically, it can cover the full transparency window of silicon (up to a wavelength of 8 μm), only requires one lithographic etch‐step and can be designed for strong light–matter interaction. Design rules, practical aspects of the fabrication process and experimental results of a complete set of elemental building blocks operating at two very different wavelengths, 3.8 and 7.7 μm, are discussed. Propagation losses as low as 0.82 dB/cm at λ 0  = 3.8 μm and 3.1 dB/cm at λ 0  = 7.7 μm are attained for the interconnecting waveguides.